EFFECTIVENESS OF EDUCATION AND MENTORING PROGRAMS IN IMPROVING MSME UNDERSTANDING OF HALAL CERTIFICATION IN PEKANBARU - Darnilawati; Afwa Ajidin, Zilal; Alchudri; Aliya Candra, Yuanit (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The implementation of halal certification is a mandatory requirement for micro and small enterprises (MSEs) as stipulated in Law Number 11 of 2020 concerning Job Creation. Although the government has provided free halal certification through the self-declare scheme, many MSEs in the food and beverage sector still face obstacles in accessing information and obtaining adequate technical assistance. This study aims to analyze the effectiveness of education and mentoring programs in improving the understanding of MSEs regarding the urgency of halal certification and to facilitate the certification process in Pekanbaru City. This research employs a pre-experimental design using the One-Group Pretest and Post-test Design approach, involving 15 food and beverage business owners in Binawidya Village, Pekanbaru. The intervention consisted of several activities, including a pre-test, educational sessions, discussions, a post-test, and technical assistance for obtaining a Business Identification Number (NIB) and self-declare halal certification. The results show a significant increase in participants’ understanding after the intervention, with the average pre-test score of 69.33 rising to 88.67 in the post-test, representing an average improvement of 19.33 points. In addition to cognitive improvement, the program also produced practical outcomes, including the issuance of halal certificates and NIBs for the assisted MSE products. The education and mentoring programs proved effective in enhancing MSEs’ comprehension of halal concepts and certification procedures, thereby promoting regulatory compliance and improving competitiveness in the market.